Polarization and Phase Control of Electromagnetic Waves in Periodic and Quasiperiodic Photonic Crystals using Fullerene and Tellurium Nanolayers - Khalid, Shalaw Saman; Ahmed, Sana Latif; Abdula, Saman Othman; Abdurahman, Shene Aziz (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
This study presents the phase control and polarization of electromagnetic waves emitted in quasiperiodic crystals such as Fibonacci, T-M, DP, and RS and the periodic structure of a photonic crystal consisting of fullerene and tellurium nanoscales in near-infrared -visible wavelengths. By examining the arrangement of layers in quasi-periodic crystals, which, like periodic structures, possess band gaps that impede the transmission of electromagnetic waves, we can determine the specific region where the photonic band gap (PBG) is formed for both transverse electric (TE) and transverse magnetic (TM) polarization waves. Subsequently, after examining the transmitted light that passed through our structure, we have identified the band gap of different structures. Also, we have plotted the phase changes in the center and edges of the band gap. After taking into account the magnitude of the electric field and the phase difference, it becomes evident that when elliptically polarized light is transmitted, a tilt angle is seen corresponding to the angle of polarization. The paper used the renowned transfer matrix approach. According to our research, the suggested design enables the creation of very condensed phase controllers, such as phase retarders and polarizers.